1965
DOI: 10.1021/bi00887a028
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Uridine Diphosphate D-Xylose. I. Uridine Diphosphate Glucuronate Carboxy-lyase of Wheat Germ*

Abstract: Uridine disphosphate D-glucuronate carboxy-lyase from wheat germ has been purified 350-fold.The only products of enzyme action are uridine diphosphate D-xylose and C02. The enzyme has a pH optimum between 6.8 and 7.0. Km for uridine disphosphate D-glucuronate is about 3 X 10~4 m. P .L olymers of D-xylose abound in higher plants. It was long suspected that the metabolic pathway in plants leading from hexose to pentose involved C-6 decarboxylation. This was substantiated by studies of many workers using either i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

1968
1968
2001
2001

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Consistent with this mechanism, previous studies of UDP-GlcA decarboxylase activity from C. laurentii indicated an absolute requirement for exogenous NAD ϩ (23). However, studies of the enzyme from wheat germ showed neither activation by NAD ϩ nor inhibition by NADH (12). Further examination of preparations from wheat germ suggested that in fact NAD ϩ is tightly bound to the enzyme, resisting even the action of NADase (12).…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…Consistent with this mechanism, previous studies of UDP-GlcA decarboxylase activity from C. laurentii indicated an absolute requirement for exogenous NAD ϩ (23). However, studies of the enzyme from wheat germ showed neither activation by NAD ϩ nor inhibition by NADH (12). Further examination of preparations from wheat germ suggested that in fact NAD ϩ is tightly bound to the enzyme, resisting even the action of NADase (12).…”
Section: Resultsmentioning
confidence: 57%
“…However, studies of the enzyme from wheat germ showed neither activation by NAD ϩ nor inhibition by NADH (12). Further examination of preparations from wheat germ suggested that in fact NAD ϩ is tightly bound to the enzyme, resisting even the action of NADase (12). Lack of NADH dissociation also explains the observed retention of tritium label at C-4 throughout a reaction postulated to proceed via a 4-keto intermediate (12,23).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations